Prevalence of anti-Leptospira antibodies in cattle confined for exportation (Research, Society and Development, 2020)
In Brazil, bovine leptospirosis is a disease of great concern, causing economic damage to livestock and an important risk to public health. In recent years, Rio Grande do Sul has consolidated itself as an important exporter of live cattle, directly reflecting on the national economy. In this context, our study aimed to determine the prevalence of anti-Leptospira antibodies in cattle destined for export, in the municipality of Pelotas / RS. A total of 4,552 animals belonging to 34 municipalities in RS were included in the study. A stratified sampling was performed and a sample of 355 sera was used in the microscopic agglutination test (MAT). Of the 355 sera sampled, 24 (6.76%; 95% CI 4.58-9.86) were reactive for at least one of the MAT antigens. No animals included in the study had a history of vaccination against leptospirosis. Serovars Hardjo and Icterohaemorrhagiae had a prevalence of 2.53%, followed by Canicola with 1.97% and Grippotyphosa with 1.12%. Our results show the exposure of cattle to the agent, which can lead to public health problems, considering that the disease is a zoonosis. Future research can use our results to plan epidemiological studies in order to describe the situation of leptospirosis in cattle herds in Rio Grande do Sul.